Secure Key Generation in Sensor Networks Based on Frequency-Selective Channels - Wilhelm, M; Martinovic, I; Schmitt, J (2013)
Key management in wireless sensor networks faces several unique challenges. The scale, resource limitations, and new threats such as node capture suggest the use of in-network key generation. However, the cost of such schemes is often high because their security is based on computational complexity. Recently, several research contributions justified experimentally that the wireless channel itself can be used to generate information-theoretic secure keys. By exchanging sampling messages during device movement, a bit string is derived known only to the two involved entities. Yet, movement is not the only option to generate randomness: the channel response strongly depends on the signal frequency as well. In this work, we introduce a key generation protocol based on the frequency-selectivity of multipath fading channels. The practical advantage of this approach is that it does not require device movement during key establishment. Thus the frequent case of a sensor network with static nodes is supported. We show the protocol's applicability by implementing it on MICAz motes, and evaluating its robustness and security through experiments and analysis. The error correction property of the protocol mitigates the effects of measurement errors and temporal effects, giving rise to an agreement rate of over 97 %. © 1983-2012 IEEE.